(untitled) (Management Studies and Business Journal (PRODUCTIVITY), 2025)
Current developments in digital technology and culture have influenced the financial behavior of Gen Z, who tend to be consumptive and oriented towards short-term gratification. In this context, frugal living has emerged as a new paradigm that continues to emphasize simplicity, efficiency, and self-control in financial management. This concept is not merely about saving, but also encompasses the ability to assess utility, delay gratification, and prioritize long-term needs over immediate desires. This study aims to examine frugal living as a strategy for early financial management for Gen Z, using the perspective of the Theory of Planned Behavior and behavioral economics. The method used is a descriptive literature review with empirical analysis of various international journals related to financial behavior, financial literacy, and frugal consumption behavior. The results of the study indicate that frugal behavior is positively correlated with financial literacy, impulse control, and individual well-being.